2007
DOI: 10.1167/iovs.06-0761
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression Prevalence Rates in Age-Related Macular Degeneration

Abstract: Self-rated depression in patients with AMD was associated with VA severity level. It should, therefore, be relatively easy for ophthalmologists to implement the screening procedure and refer identified patients to psychiatrists for proper assessment and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
3
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(137 citation statements)
references
References 37 publications
9
113
3
12
Order By: Relevance
“…Consistent with previous research [17][18], themes emerging from patients' narratives as well as the high frequency of depression in this sample suggest poor quality of life and dramatically altered self-perceptions following vision loss in adulthood. Furthermore, current participants reported a frequency of depression (39.5%) similar to previous studies [6][7]9,44].…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with previous research [17][18], themes emerging from patients' narratives as well as the high frequency of depression in this sample suggest poor quality of life and dramatically altered self-perceptions following vision loss in adulthood. Furthermore, current participants reported a frequency of depression (39.5%) similar to previous studies [6][7]9,44].…”
Section: Discussionsupporting
confidence: 87%
“…Many studies showed that during the developmental stage of children and adolescents with visual impairment, they continue becoming more vulnerable to life circumstances [9]. Low vision is associated with negative consequences such as limitations in day-to-day activities [10,11], poor physical function [10], depressive symptoms [12][13][14][15][16], and low quality of life [17]. There is an internal relationship between sensory impairment, mental and social functioning, and communication [18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [11][12][13][14][15][16] have stated high rates of depression in people with impaired vision. But only a few researches conducted on visually impaired people have accredited the role of psychological interventions in reducing depression in this group.…”
Section: Introductionmentioning
confidence: 99%
“…It is the fourth major cause of disability worldwide [27] and a common side effect in people with vision loss [28][29][30][31][32][33]. Multiple studies have found close to a 30% prevalence rate of depression among elderly patients with advanced AMD, [27,34] and these patients are at an increased risk of suicide [35].…”
Section: Depressionmentioning
confidence: 99%